Traumatic tension enterothorax in New Zealand: a case report - Monique Mahadik; Ashok Gunawardene; Aleisha Sutherland; Damien Ah Yen (Journal of Trauma and Injury)
Traumatic rupture of the right hemidiaphragm occurred following a high-velocity motor vehicle collision in the case presented herein. The resulting herniation of small bowel loops into the thorax resulted in hemodynamic and respiratory compromise due to pressure effects on the right heart and major vessels. The patient’s hemodynamic status improved with reduction of enterothorax, and the diaphragmatic defect was repaired. We discuss the available literature and learning points from this rare case.